급성 전방십자인대 손상 환자에서 보존적 치료의 임상적 결과 - 최의성(Eui Sung Choi); 박상준(Sang Jun Park) (The journal of the Korean Orthopaedic Association, 2016)
목적: 급성 전방십자인대 손상 환자에서 보존적 치료의 임상적 결과를 알아보고자 하였다. 대상 및 방법: 2010년 1월부터 2013년 5월까지 급성 전방십자인대 손상 환자 중 보존적 치료를 시행한 49예를 대상으로 하였고, 모두 자기공명영상장치를 통하여 파열을 확인하였다. 남성 39명, 여성 10명이며, 평균연령은 37.6세였고, 부분 파열 16예, 완전 파열은33예였다. 보존적 치료는 장하지 석고붕대를 6주간 시행 후, 대퇴사두근 및 슬괵근의 등장성 운동을 시행하였다. 결과: 49예 중 통증과 불안정감으로 인하여 3예에서 수술적 치료를 시행하였다. 보존적 치료를 지속한 46예에서 최종 추시(평균12.9개월) 시 30도 슬관절 굴곡상태에서 Telos 기기를 이용한 전방 스트레스방사선 검사상 양측 전방전위의 차이로 슬관절 불안정성을 평가하였고, 그 수치는 평균 2.74±1.36 mm (0.51-7.46 mm), Tegner 활동도 점수는 평균 6.30±0.92점(3-8점), International Knee Documentation Committee 점수는 평균 84.7±13.11점(51.7-97.7점)이었다. 결론: 자기공명영상상 급성 전방십자인대 파열이 확인된 경우, 적절한 환자군에서는 보존적 요법으로도 일상생활에 지장을 주지 않는 정도의 기능회복이 가능할 것으로 생각된다 Purpose: We evaluate the clinical results of conservative treatment in patients with acute anterior cruciate ligament (ACL) injury. Materials and Methods: From January 2010 to May 2013, 49 patients with acute ACL injury who received conservative treatment were selected as subjects. All ruptures were diagnosed by magnetic resonance imaging (MRI). Sixteen patients had partial ruptures and 33 patients had complete ruptures. The average age was 37.6 years; males were 39, and females were 10. Conservative treatment included a long leg cast for 6 weeks and isotonic exercise for quadriceps and hamstring. Knee joint instability was evaluated with the side-to-side difference using the Telos device. Tegner activity score, International Knee Documentation Committee (IKDC) subjective score, and range of motion in the joint were assessed in all patients. Results: In the final follow-up, the mean value of the Tegner activity score was 6.30 points (3-8 points), and the mean value of the IKDC score was 84.7 points (51.7-97.7 points). The mean value of side-to-side difference using the Telos device was 2.74 points (0.51-7.46 points). Conclusion: Our study suggests that acute ACL injury diagnosed by MRI can be treated conservatively in appropriate patients, with favorable results. KCI Citation Count: 3